Switchable Fluorescent and Solvatochromic Molecular Probes Based on 4-Amino-N-methylphthalimide and a Photochromic Diarylethene - Yan, Sergey F. (2008)
New fluorescent photochromic compounds (1-H and 1-Boc)have been synthesized and characterized in different solvents.The fluorescence emission can be switched “on” and“off” with visible light and UV, respectively, by means of thephotochromic reaction. The emission wavelength and efficiencystrongly depend on the polarity of the solvent. Thecompounds show a positive solvatochromic effect in theemission maxima, and their fluorescence quantum yield decreasesas the solvent’s polarity increases (from cyclohexaneto dioxane). In solvents more polar than dioxane the emissionis too weak and therefore undetectable, and thus 1-H and 1-Boc behave as “normal” photochromic compounds. The photochromic reaction is also sensitive to the environment. A decreaseof more than an order of magnitude was found for thequantum yield of the colouring reaction (ΦOFCF) for 1-H inethanol compared with cyclohexane, and an about threefolddecrease in ΦOFCF was observed for the compound 1-Bocin polar solvents (compared with apolar solvents). For bothcompounds the ring-opening reaction was found not to dependenton the solvent. The novel fluorescent molecularswitches 1-H and 1-Boc are able to probe the polarity of theirmicroenvironment.